Monitoring complex financial instruments in banks' balance sheets - Jannis Bischof; Rainer Haselmann; Tobias Tröger (Leibniz Institute for Financial Research SAFE, 2022)
European banks have substantial investments in assets that are measured without directly observable market prices (mark-tomodel). Financial disclosures of these value estimates lack standardization and are hard to compare across banks. These comparability concerns are concentrated in large European banks that extensively rely on level 3 estimates with the most unobservable inputs. Although the relevant balance sheet positions only represent a small fraction of these large banks' total assets (2.9%), their value equals a significant fraction of core equity tier 1 (48.9%). Incorrect valuations thus have a potential to impact financial stability. 85% of these bank assets are under direct ECB supervision. Prudential regulation requires value adjustments that are apt to shield capital against valuation risk. Yet, stringent enforcement is critical for achieving this objective. This document was provided by the Economic Governance Support Unit at the request of the ECON Committee.
Keywords: 330; Bank's Balance Sheets; Complex Financial Instruments